Local economic development in the indigenisation era: case of Mazowe Rural District Council - Tapi, Cliff (Midlands State University, 2017)
Zimbabwe is rated as one of the poorest countries in the world, a scary fact considering that the country is endowed with vast mineral resources like diamonds, natural gas and gold which if effectively used could make it have one of the strongest economies on the continent. In order to make this possible, there is a need to ensure that growth at a local level is fostered by the central government and this growth should be uniform so as to ensure that there is no concentration of development in one place. The historical overview of development challenges in Zimbabwe were categorised into three distinct epochs that is the early independence era (1980-1990), liberalisation era (1991-1999) and Post Movement for Democratic Change (MDC) era (2000 to date). The main purpose of the research was to analyse whether there has been any meaningful contribution by the indigenisation policy to local economic development and the basis to the research was underpinned by three main objectives of the identification of the indigenisation projects in Mazowe district, an analysis of success and failures of the indigenisation projects and subsequently an analysis of the impact of indigenisation on local economic development of Mazowe. Although the research was case study based, it also made use of regional and international examples all in a bid to analyse whether the problems to development and abatement strategies thereafter being faced in Zimbabwe were similar to the ones faced in South Africa and Malaysia. The research made use of the area of Mazowe District which has around 232 000 inhabitants and derived a population sample of about 150 people. The research made use of both probability and non-probability sampling methods to ensure representativeness with purposive sampling, stratified random sampling, convenience and systematic random sampling being used. Data for the research was acquired through a combination of primary and secondary data sources. Primary data made use of self-administered questionnaires as well as interviews with secondary data mainly derived from council documents. Major research findings accrued from the field indicate that the indigenisation policy has had a positive impact on LED with the indigenous people having ownership of their resources through the land reform as well as ownership of small mining claims. Observations also made were that there was a booming informal sector that has largely been underutilised by the local authority and given the right policies could contribute significantly to the development of the area. On the lop side, it was observed that the infrastructure in the area is poor and unevenly balanced leading to development disparities. The researcher recommends among other things that there be capacity building for small scale miners and the informal sector which will make these contribute significantly to LED.